Asteroseismic inference on rotation, gyrochronology and planetary system dynamics of 16 Cygni. Issue 3 (29th November 2014) - Davies, G. R.; Chaplin, W. J.; Farr, W. M.; García, R. A.; Lund, M. N.; Mathis, S.; Metcalfe, T. S.; Appourchaux, T.; Basu, S.; Benomar, O.; Campante, T. L.; Ceillier, T.; et al.
Abstract: The solar analogues 16 Cyg A and B are excellent asteroseismic targets in the Kepler field of view and together with a red dwarf and a Jovian planet form an interesting system. For these more evolved Sun-like stars we cannot detect surface rotation with the current Kepler data but instead use the technique of asteroseimology to determine rotational properties of both 16 Cyg A and B. We find the rotation periods to be 23.8^+1.5_-1.8 and 23.2^+11.5_-3.2 d, and the angles of inclination to be 56^+6_-5 ^° and 36^+17_-7 ^° , for A and B, respectively. Together with these results we use the published mass and age to suggest that, under the assumption of a solar-like rotation profile, 16 Cyg A could be used when calibrating gyrochronology relations. In addition, we discuss the known 16 Cyg B star–planet eccentricity and measured low obliquity which is consistent with Kozai cycling and tidal theory.